2022
DOI: 10.3389/fphar.2021.797541
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Protects Striatal Cells and Improves Motor Function in Huntington’s Disease Models: Role of PAC1 Receptor

Abstract: Huntington’s disease (HD) is a hereditary neurodegenerative disorder caused by the expression of mutant huntingtin (mHtt). One of the main features of HD is the degeneration of the striatum that leads to motor discoordination. Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide that acts through three receptors named PAC1R, VPAC1R, and VPAC2R. In the present study, we first investigated the effect of PACAP on STHdhQ7/Q7 and STHdhQ111/Q111 cells that express wild-type Htt with 7 and mHt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 103 publications
1
8
0
Order By: Relevance
“…Interestingly, activation of GHRH-R promotes cAMP elevation, which has been implicated in the protective effect of GHRH and its agonistic analogs in different in vitro and in vivo models of disease, including ischemic stroke and neurodegeneration ( 17 , 19 , 23 , 26 , 28 ). Moreover, GHRH belongs to the family of the so-called brain-gut peptides, which also includes pituitary adenylate cyclase-activating polypeptide, a neuropeptide with beneficial effects in models of spinal cord injury, spinal and bulbar muscular atrophy and Huntington disease, acting via cAMP-mediated mechanisms ( 15 , 53 ). Although we did not address it in this study, we assume that the cAMP pathway may be involved in the protective effects of MR-409, along with others activated by GHRH-R, such as PI3K/Akt, GSK-3b, mTOR, and MAPK/ERK ( 19 , 21 , 28 ), which are also protective in SMA ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activation of GHRH-R promotes cAMP elevation, which has been implicated in the protective effect of GHRH and its agonistic analogs in different in vitro and in vivo models of disease, including ischemic stroke and neurodegeneration ( 17 , 19 , 23 , 26 , 28 ). Moreover, GHRH belongs to the family of the so-called brain-gut peptides, which also includes pituitary adenylate cyclase-activating polypeptide, a neuropeptide with beneficial effects in models of spinal cord injury, spinal and bulbar muscular atrophy and Huntington disease, acting via cAMP-mediated mechanisms ( 15 , 53 ). Although we did not address it in this study, we assume that the cAMP pathway may be involved in the protective effects of MR-409, along with others activated by GHRH-R, such as PI3K/Akt, GSK-3b, mTOR, and MAPK/ERK ( 19 , 21 , 28 ), which are also protective in SMA ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in this review, these protective effects are suggested to be indirectly linked via the inhibition of downstream pro-apoptotic effectors of different UPR branches and the elevation of anti-apoptotic molecules, or possibly directly linked to the inhibitory activities of ER stress key players. Overall, it can be implied that there remains much to explore and consider regarding the role of PACAP/VIP system in the modulation of ER stress responses produced in the demyelinating CNS [90,139]. The bidirectionality of this regulatory activity is suggested to be a plausible theory, in which chronic ER stress could downregulate the endogenous expression of PACAP/VIP receptors, thereby reducing the endogenous ability of PACAP/VIP to afford neuroprotection; this must be clarified via further experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat encouragingly, the positive effects of P42 are potentiated by habitat enrichment in this model, an environmental modification that is well-connected with a beneficial BDNF response [ 246 ]. Another group reported that the intranasal administration of a recombinant vasoactive intestinal peptide (VIP) upregulated striatal BDNF in the R6/1 model, likely through coupling with the cAMP–PKA–CREB pathway ( Figure 2 ) [ 247 ]. In summary, advancements in neurotrophin drug discovery and delivery will unlock previously inaccessible therapeutic options for the treatment of HD and various neurodegenerative diseases.…”
Section: Bdnf-focused Therapeutic Approaches For Hdmentioning
confidence: 99%